Generating interval and semi-order extensions of partially ordered sets - Figueiredo, Celina; Queiroz, Aquiles (Cadernos do IME - Série Informática, 2022)
This is an account of the collaboration and the research conduction by Prof. Jayme Luiz Szwarcfiter, during the development of the thesis of Aquiles Braga de Queiroz at COPPE/UFRJ, "Algoritmos para a Geração de Classes de Extensões de Conjuntos Parcialmente Ordenados", completed in 2005.